Medicaid and household savings behavior: New evidence from tax refunds - Gallagher, Emily A.; Gopalan, Radhakrishnan; Grinstein-Weiss, Michal; Sabat, Jorge (Journal of Financial Economics, 2020)
Using data on over 57,000 low-income tax filers, we estimate the effect of Medicaid access on the propensity of households to save or repay debt from their tax refunds. We instrument for Medicaid access using variation in state eligibility rules. We find substanital heterogeneity across households in the savings response to Medicaid. Households that are not experiencing financial hardship behave in a manner consistent with a precautionary savings model, meaning they save less under Medicaid. In contrast, among households experiencing financial hardship, Medicaid eligibility increases refund savings rates by roughly 5 percentage points or $102. For both sets of households, effects are stronger in states with lower bankruptcy exemption limits—consistent with uninsured, financially constrained households using bankruptcy to manage health expenditure risk. Our results imply that expansions to the social safety net may affect the magnitude of the consumption response to tax rebates.